Pengaruh Konsumsi Vitamin C dan Konsumsi Air terhadap Kelelahan Subjektif pada Pekerja Perempuan Pembuatan Genting: The Impact of Vitamin C Intake and Water Consumption on Perceived Fatigue among Female Tile Workers - Sahiroh, Eli; Denny, Hanifa M.; Setyaningsih, Yuliani; Lestantyo, Daru; Suroto, Suroto (Universitas Airlangga, 2025)
Background: The tile industry is known for its demanding nature, primarily due to the high energy requirements involved. The manual production methods necessitate significant physical exertion, including the lifting and transportation of heavy, large tiles. This can lead to fatigue as a result of lactic acid buildup in the muscles. Research indicates that burnout rates among workers in the tile industry can reach as high as 82%. Objectives: To analyze the effect of vitamin C consumption and drinking water consumption on perceived fatigue levels among female workers in the tile manufacturing sector. Methods: This research employed a quasi-experimental design, involving a sample of 52 female workers engaged in tile production for each group. Each group participated in an experimental procedure lasting 6 days, after which they were assessed for levels of fatigue. The independent variables examined were the intake of Vitamin C and water, while the dependent variable was the participants' subjective experience of fatigue. Subjective fatigue was quantified using the Work Fatigue Feelings Measurement Questionnaire (KAUPK2). The statistical methods applied included the Wilcoxon Test and the Kruskal-Wallis test. Results: The findings indicated that both Vitamin C intake and water consumption significantly influenced subjective fatigue levels before and after the intervention (p-value=0.000). Based on the results of the analysis before being given vitamin C, the subjective fatigue score was 51 after being given vitamin C, it dropped to 25. In contrast, before the introduction of drinking water, the subjective fatigue score was 48.23, which subsequently fell to 31.52 after water consumption. The analysis revealed a notable difference in the average subjective work fatigue scores post-intervention. Conclusions: The intake of Vitamin C and adequate water consumption effectively reduces subjective work fatigue among female tile-making workers. Consequently, it is recommended that industry owners ensure the provision of sufficient drinking water and Vitamin C for their employees.